Regulation of oxytocin-induced calcium transients and gene expression in engineered myometrial tissues by tissue architecture and matrix rigidity - Antonina P. Maxey; Jaya M. Travis; Megan L. McCain (Current Research in Physiology, 2023)
The uterus is susceptible to benign tumors known as fibroids, which have been associated with many pregnancy complications, including preterm labor. However, the impact of fibrotic tissue remodeling on the physiology of the myometrium, the smooth muscle layer of the uterus, is poorly understood, in large part due to a lack of model systems. In this study, we engineered healthy-like and fibrotic-like myometrium by culturing human myometrial smooth muscle cells on polyacrylamide hydrogels micropatterned with fibronectin to independently tune matrix rigidity and tissue alignment, respectively. We then evaluated calcium transients in response to oxytocin stimulation. Isotropic myometrial tissues on stiff substrates (representing fibrotic myometrium) had shorter calcium transients due to shorter decay time compared to aligned myometrial tissues on soft substrates (representing healthy myometrium). Calcium transients in aligned tissues had longer response times and longer decay times than isotropic tissues, irrespective of substrate stiffness. The amplitude of calcium transients was also higher on soft substrates compared to stiff substrates, irrespective of tissue alignment. We also performed RNA sequencing to detect differentially expressed genes between healthy- and fibrotic-like tissues, which revealed that a bitter taste receptor shown to induce smooth muscle relaxation, TAS2R31, was down-regulated in fibrotic-like tissues. Finally, we measured oxytocin-induced calcium transients in response to pre-treatment with progesterone, caffeine, thrombin, and nifedipine to demonstrate applications for our model system in drug screening. Both progesterone and caffeine caused a decrease in calcium transient duration, as expected, while thrombin and nifedipine had less impact. Collectively, our engineered model of the myometrium enables new insights into myometrial mechanobiology and can be extended to identify or screen novel drug targets.